2019
DOI: 10.1111/1556-4029.13995
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Protein‐based Human Identification Capability from a Single Hair

Abstract: Shed human hair (lacking root nuclear DNA) frequently contributes important information to forensic investigations involving human identification. Detection of genetic variation observed in amino acid sequences of hair proteins provides a new suite of identity markers that augment microscopic hair analysis and mitochondrial DNA sequencing. In this study, a new method that completely dissolves single hairs using a combination of heat, ultrasonication, and surfactants was developed. Dissolved proteins were diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…These sequences along with corresponding nonvariant sequences are listed in Appendix S3. Table shows the specific GVP identification for the three methods with three replicate runs for each method, namely our direct method, the modified NaOH + SDS method , and the cleavable surfactant method . For both the direct method and modified NaOH + SDS method, GVP panel results from different fractions are combined in Table .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These sequences along with corresponding nonvariant sequences are listed in Appendix S3. Table shows the specific GVP identification for the three methods with three replicate runs for each method, namely our direct method, the modified NaOH + SDS method , and the cleavable surfactant method . For both the direct method and modified NaOH + SDS method, GVP panel results from different fractions are combined in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The publication by Parker et al showed that these peptides might serve as a source of evidence in addition to DNA for human identification due to several advantages that a hair sample carries: (i) commonly found—on average, humans shed 50–150 hairs per day; (ii) stable—proteins in a hair sample usually last longer and are more resistant to degradation than DNA; and (iii) when good quality DNA is not available, hair proteins may serve as alternative evidence by detecting those GVPs in hair cuticular keratins and other hair proteins. A recent publication by Mason et al described protein‐based or GVP‐based human identification from a single hair as short as 1 inch long. Another recent publication by Carlson et al described a sensitive method to extract proteins from 1 millimeter or less in total length of human anagen head hairs and compared the proteins identified from hair shaft and hair root.…”
mentioning
confidence: 99%
See 3 more Smart Citations